A common polymorphic variant of UGT1A5 displays increased activity due to optimized cofactor binding. Issue 11 (22nd May 2018) - Yang, Fan; Machalz, David; Wang, Sisi; Li, Zhengyi; Wolber, Gerhard; Bureik, Matthias
Abstract : Uridine diphosphate‐glucuronosyltransferases (UGTs) are the most important phase II enzymes in human drug metabolism. Using permeabilized recombinant fission yeast cells (enzyme bags), we demonstrate that UGT1A5 can catalyze an N ‐glucuronidation reaction. We characterized two new polymorphic UGT1A5 variants: a common ninefold mutant (UGT1A5*8) with double‐fold activity and a much rarer sixfold mutant (UGT1A5*9), which has the same activity as the wild‐type. Molecular modeling studies indicate that the minor effects of all mutations, except for Gly259Arg, are due to their distance to the substrate binding site. Extensive molecular dynamics simulations revealed that the Gly259Arg mutation stabilizes helix Q through a newly formed hydrogen bonding network, which places the cofactor in a much more favorable geometry in UGT1A5*8 as compared to the wild‐type. Abstract :